Statement of Peer Review - Juliana Gerard; Morgan Macleod; Adina Camelia Bleotu; Muskaan Singh (Proceedings)
In submitting conference proceedings to Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]